1988
DOI: 10.1007/bf01541811
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of Nocturnal Penile Tumescence and penile response to erotic stimulation during waking states in comprehensively diagnosed groups of males experiencing erectile difficulties

Abstract: The erectile responses of 13 nondysfunctional males and 48 dysfunctional males were compared during Nocturnal Penile Tumescence (NPT) and during exposure to erotic videotapes. The results showed distinct patterns of NPT and daytime responding that could differentiate the various subgroups: those displaying (i) no dysfunction; (ii) vasculogenic erectile dysfunction; (iii) high risk for erectile dysfunction (organic and psychogenic); (iv) psychogenic dysfunction; reactive to erotica; and (v) psychogenic dysfunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1988
1988
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Because it is known that physiological and psychological factors may affect both sleep and waking-state erections, it appears that waking-state tumescence assessment constitutes a more direct and appropriate measure of actual sexual performance. This conclusion is corroborated by the findings of a recent study by Wincze and his associates, who examined erectile response in relatively homogeneous diagnostic groups of dysfunctional men and in nondysfunctional controls during both sleep and daytime assessment (Wincze et al, 1988). These investigators demonstrated that NPT results are not representative of the maximum erectile response possible and that exposure to erotic stimuli may override organic deficits in some cases.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Because it is known that physiological and psychological factors may affect both sleep and waking-state erections, it appears that waking-state tumescence assessment constitutes a more direct and appropriate measure of actual sexual performance. This conclusion is corroborated by the findings of a recent study by Wincze and his associates, who examined erectile response in relatively homogeneous diagnostic groups of dysfunctional men and in nondysfunctional controls during both sleep and daytime assessment (Wincze et al, 1988). These investigators demonstrated that NPT results are not representative of the maximum erectile response possible and that exposure to erotic stimuli may override organic deficits in some cases.…”
supporting
confidence: 64%
“…As a measure of general capacity for sexual expression in the older men of our sample, Snap-Gauge NPT certainly did not provide a sufficiently accurate reflection of waking-state adjustment. As the findings of Wincze et al (1988) demonstrated in a younger sample, it seems that determination of organic versus psychogenic etiology for erectile dysfunction, especially in older men, cannot be based on even a detailed examination of NPT parameters alone. The etiology of "normal" age-related changes in the pattern of sleep-related erections has not yet been identified, and the results of the present study indi- cate minimal concordance between "impairment" assessed using Snap-Gauge NPT and waking-state sexual adjustment.…”
Section: Discussionmentioning
confidence: 94%
“…40 At this time the most reliable technique by which to diagnose a psychogenic basis for the erectile problem is measurement of penile tumescence 43 or rigidity 44 (or both) during sleep or erotic arousal. 45 The presence of intact nocturnal erectile responses in a patient with erectile complaints establishes a diagnosis of psychogenic impotence. These patients may improve with reassurance and a better understanding of the hypotensive drugs; unresponsive patients may require referral for formal sex therapy.…”
Section: Evaluation Of Sexual Functionmentioning
confidence: 99%
“…In an often cited study, Wincze et al (1988) contrasted NPT profiles taken during sleep and while patients viewed an erotic videotape. Results suggested stronger erections to the videotape, but no measures of penile rigidity were taken.…”
Section: Current Methodsmentioning
confidence: 99%